Implementation of big data analytics and Manufacturing Execution Systems: an empirical analysis in German-speaking countries. Issue 2 (17th February 2022) - Wiech, Michael; Boffelli, Albachiara; Elbe, Christian; Carminati, Paolo; Friedli, Thomas; Kalchschmidt, Matteo
Abstract: Many firms have started Industry 4.0 (I4.0) initiatives in recent years, without having a sound understanding of the effects generated by the technologies introduction. This research provides indications of what to expect from the implementation of two key technologies for I4.0: big data analytics and manufacturing execution systems. The study explores the relationships between these technologies' implementation and a set of performance effects. Additionally, it analyses the influence of the organisational structure. A set of hypotheses derived from literature builds the basis for the quantitative analysis of an industry survey with 116 participants from German-speaking countries. The results show that these technologies have distinct, partially unexpected, performance effects. Furthermore, this research provides evidence that the organisational structure of technology implementation plays no significant role in the attainment of higher technology implementation levels.